Chemical constituents and neuroprotective effect of the selected plants of Sarawak, Calophyllum gracilentum and Calophyllum recurvatum / Nurr Maria Ulfa Seruji - Ulfa Seruji, Nurr Maria (2024)
Calophyllum species is well known due to its abundance of potentially beneficial phytochemicals, such as xanthones, coumarins, and others. Despite the extensive report on the rich source of phytochemicals and their biological activities from Calophyllum, Calophyllum gracilentum and Calophyllum recurvatum from the Sarawak Forest is relatively unknown due to the limited information available. A phytochemical study conducted on the stem bark extracts of Calophyllum gracilentum successfully afforded two new xanthones, namely marixanthone I (CG9) and marixanthone II (CG10) together with ten other known xanthones namely brasixanthone B (CG1), trapezifolixanthone (CG2), bracteaxanthone XII (CG3), caloxanthone I (CG4), pyranojacareubin (CG5), 5-methoxytrapezifolixanthone (CG6), caloxanthone A (CG7), brasilixanthone B (CG8), 9-hydroxycalabaxanthone (CG11), pancixanthone B (CG12) and, three chromanone acids, isocalolongic acid (CG13), isoblanchoic acid (CG14) and apetalic acid (CG15) also two triterpenoids, friedeline (CG16) and lupeol (CG18) and a phytosterol, β-sitosterol (CG17). Meanwhile, a total of six compounds were isolated from C. recurvatum, namely trapezifolixanthone (CR1), 6deoxyjacareubin (CR2), ananixanthone (CR3), thwaitesixanthone (CR4), friedeline (CR5) and stigmasterol (CR6). The total phenolic content and total flavonoid content tests showed that both species contain high to moderate levels of phenolic and flavonoid content and antioxidant free radical scavenging assay showed that the extracts exhibited significant activity. Moreover, the evaluation of their neuroprotective properties has been the least studied. Hence, this study is aimed to find and investigate potential therapeutic agents especially for Alzheimer’s and Parkinson’s disease treatment derived from Calophyllum gracilentum and Calophyllum recurvatum in accordance with the goal. Overall, the findings have highlighted the therapeutic potential of CR4, CR5, CR6, CG3, and CG12 as neuroprotective agents as supported by the molecular docking analysis and the structure-activity relationship (SAR) analysis has led to structural features underlying the positive interactions of the tested compounds with specific protein receptors, providing further insight into the mechanisms underlying their biological activities.